Follow-up of a social skills training (SST) for juvenile delinquents: effects on reoffending - van der Stouwe, Trudy (Journal of experimental criminology, 2019)
To examine (1) the long-term effects on reoffending of an individual SST for juvenile delinquents in The Netherlands and (2) whether effects differ by demographic and offense history characteristics.